Strategi Public Relations Metro TV dalam Membentuk Opini Publik melalui Program Meet Nite Live - Nathan Andrew Anindito; Zon Vanel (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze Metro TV’s Public Relations strategies in shaping public opinion through the Meet Nite Live program. This study employed a qualitative approach with a case study method. This study gathered data through interviews with seven informants (comprising the creative team, presenters, and active viewers), supplemented by observations and analyses of digital content. Data analysis followed the interactive model of Miles, Huberman, and Saldaña via data condensation, display, and conclusion drawing. The findings indicate that Metro TV's PR strategies are systematically implemented across four stages. Research and listening serve as the foundation for the curation of socio-political issues and mapping of digital audience preferences. Planning and Decision designs a satire-based news-tainment hybrid under editorial supervision. Communication and Action executes cross-platform media convergence and provides two-way interactive spaces, such as the SEBAT segment. Finally, Evaluation adaptively monitors engagement metrics, follower growth, and audience sentiment. Consequently, the program successfully enhances audience engagement and gradually shapes public opinion through cumulative shifts in viewers perceptions, attitudes, and viewpoints. This study contributes to media PR scholarship by demonstrating that public opinion in the digital era is co-constructed through media communication strategies and active audience participation within the digital public sphere.